Literature and citizenship in the age of revolution : a wish for air and liberty - Gauvin, Mitchell, 1989- (New York, NY : Routledge, 2025)
"Citizenship is at the forefront of popular imagination as political movements and state governments around the world traffic in anti-immigrant rhetoric and call for increased policing of borders. A Wish for Air and Liberty looks back to a critical historical juncture in the development of citizenship to uncover how literature contoured and contested imaginings of citizenship. While territory and the nation-state often frame our understandings of citizenship, this book focuses on how non-citizens, foreigners, and strangers have long been central for citizenship's coherence. Rather than rootedness, literary texts exposed the circulations of persons, ideas, and emotions at the heart of citizenship. This book brings together an unlikely combination of writers-Olaudah Equiano, Jane Austen, Mary Shelley, and Herman Melville-to shows how literature in the Age of Revolution exposed contradictions in notions of liberty and slavery that impacted how citizenship was conceived and practiced"--
Keywords: Citizenship in literature; Literature and society; English literature -- 19th century -- History and criticism; American literature -- 19th century -- History and criticism; LITERARY CRITICISM / American / General; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; HISTORY / United States / Revolutionary Period (1775-1800)